2014
DOI: 10.1007/s00411-014-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and chromosomal aberrations in hMTH1-transfected and non-transfected TK6 cells after exposure to low dose rates of gamma radiation

Abstract: The aim of the present study was to analyse the dose rate effect of gamma radiation at the level of mutations, chromosomal aberrations, and cell growth in TK6 cells with normal as well as reduced levels of hMTH1 protein. TK6 cells were exposed to gamma radiation at dose rates ranging from 1.4 to 30.0 mGy/h (chronic exposure) as well as 24 Gy/h (acute exposure). Cell growth, frequency of thymidine kinase mutants, and of chromosomal aberrations in painted chromosomes 2, 8, and 14 were analysed. A decline in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Numerous results have demonstrated that reducing the dose rate below the HDR range exerts a sparing effect on cell killing due to improved repair of sub-lethal damage (Badie et al 1996 ; Bedford et al 1978 ). For the same reason, the frequency of unstable chromosomal aberrations and micronuclei is reduced per unit dose when the dose rate is reduced below HDR (Bauchinger et al 1979 ; Manesh et al 2014 ; Tanaka et al 2009 ; Vral et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous results have demonstrated that reducing the dose rate below the HDR range exerts a sparing effect on cell killing due to improved repair of sub-lethal damage (Badie et al 1996 ; Bedford et al 1978 ). For the same reason, the frequency of unstable chromosomal aberrations and micronuclei is reduced per unit dose when the dose rate is reduced below HDR (Bauchinger et al 1979 ; Manesh et al 2014 ; Tanaka et al 2009 ; Vral et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Later, animal studies on cancer and non-cancer stochastic effects confirmed the existence of DDREF (reviewed in Little 2018 ). Results of cell experiments which focused on mutations and stable-type chromosomal aberrations that can be regarded as molecular events related to cancer (Beroukhim et al 2007 ) are contradictory, with some showing no or little sparing effect of LDR (Evans et al 1990 ; Manesh et al 2014 ) and other demonstrating clear effects (Kiefer et al 2002 ) (reviewed in Manesh et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endpoints such as chromosomal aberrations and mutations have been assessed at dose rates as low as 20 mGy/d with accumulated doses of 8 Gy [ 13 ]; more commonly dose rates of 1–10 mGy/h are reported with accumulated doses of 0.5 to several Gray (e.g. Okudaira et al [ 14 ]; Manesh et al [ 15 ]). Reference [ 16 ], a review specifically considering cellular and molecular data suitable for dose rate effect evaluation, provides a more extensive summary and tabulation of the irradiation conditions used in the relevant studies.…”
Section: Dose Rates and Corresponding Cumulative Doses Typically Usedmentioning
confidence: 99%